2021
DOI: 10.3389/fonc.2020.614096
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Ex Vivo Culture for Drug Responses of Patient-Derived Gastric Cancer Tissue

Abstract: Gastric cancer (GC) is one of the most common malignancies with high mortality and substantial morbidity. Although the traditional treatment strategies for GC revolve around surgery, radiotherapy, and chemotherapy, none have been able to optimally treat most affected patients. To improve clinical outcomes and overcome potential GC resistance, we established a three-dimensional (3D) culturing platform that accurately predicts drug responses in a time- and cost-effective manner. We collected tumor tissues from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…PDOs of GC could be cultured from both tissue specimens and malignant ascites (Table 4) [40][41][42][43]. Gao et al developed 15 GC PDOs from 5 patients and identified similar KRAS alterations and drug sensitivity in primary tumours and paired organoids [41].…”
Section: Organoid and Pdx Models In Gc The Culture And Application Of...mentioning
confidence: 99%
“…PDOs of GC could be cultured from both tissue specimens and malignant ascites (Table 4) [40][41][42][43]. Gao et al developed 15 GC PDOs from 5 patients and identified similar KRAS alterations and drug sensitivity in primary tumours and paired organoids [41].…”
Section: Organoid and Pdx Models In Gc The Culture And Application Of...mentioning
confidence: 99%
“…In addition, 3D culture systems can simulate the TME of CSCs by controlling the mechanical properties of materials and then effectively isolate CSCs. Recently, increasing studies have also used 3D culture systems to isolate and culture GCSCs (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Also, with the advancement of bioengineering techniques and microfluidics, the 3D culture method of PDCs has the advantages of being easily reproducible and applicable to a high-throughput platform while maintaining the diversity of patient-native cancer tissues [ 11 , 12 ]. Thus, it is widely applied to research on cancer mechanisms and responsiveness to various anticancer treatments [13] , [14] , [15] , [16] . However, most previous studies regarding response to RT have been performed using tumor tissues stored in a biobank or grown in mice (PDX, patient-derived xenograft).…”
Section: Introductionmentioning
confidence: 99%